The Impact of Sustainability Reports on the Financial Performance of Banking Companies Listed on the Indonesia Stock Exchange 2019-2023 - Nur Azizah; Enggar Diah Puspa Arum; Rico Wijaya Z. (Journal of Innovative and Creativity, 2025)
This study aims to analyze the influence of sustainability reports on the financial performance of banking companies listed on the Indonesia Stock Exchange from 2019 to 2023. Sustainability reports are measured using the level of disclosure based on the Global Reporting Initiative (GRI) standards on economic, environmental, and social performance, while financial performance is proxied by Return on Assets (ROA). This study uses a quantitative approach with Structural Equation Modeling analysis. Partial Least Squares (SEM-PLS) analysis. The results show a negative effect on sustainability reporting, environmental performance, and social performance, and an insignificant positive effect on economic performance. These findings indicate that the integration of sustainability into bank business strategies is not yet optimal, and the market has not yet fully financially recognized the sustainability efforts undertaken by the banking industry.